Zatoichi's conspiracy [videorecording (DVD)] - Yasuda, Kimiyoshi, 1911-1983; Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Shimura, Takashi, 1905-1982; Satō, Kei, 1928-2010; Shimozawa, Kan, 1892-1968 (AnimEigo, 2004)
"The flip of a coin leads the blind masseur and master swordsman Zatoichi to his hometown, a place he has not visited in over two decades. Despite his extended hiatus, he finds that several people remember him from his hellcat youth, including a 'sister' that he never knew he had and the village's local government Superintendant. But things never stay quiet for the masseur for very long. An old face from Ichi's childhood, Shinbei, has hatched a nefarious plot to rob the town of thier valuable community quarry. The masseur is caught in the unenviable position of mediating the conflict between his former pal and the home of his youth, with neither side willing to budge. Can Ichi,the champion of the weak and oppressed, do the right thing, even if it pits him against his childhood chum?"--Container. The 25th movie in the series.